Construction of graphdiyne (CnH2n-2) based Co-S-P/CuI double S-scheme heterojunctions proved with in situ XPS characterization for efficient photocatalytic hydrogen production. (April 2023) - Zhang, Yueyang; Liu, Hai; Yang, Mengxue; Li, Songling; Jin, Zhiliang
Highlights: GDY/CuI binary heterojunction is prepared by the one-pot method. The ternary heterojunction (Co-S-P/GDY/CuI) catalysts are prepared. Highly improved photocatalytic hydrogen evolution activity is obtained over Co-S-P/GDY/CuI double-S scheme heterojunctions. The effect of GDY on the hydrogen precipitation activity is proved through a series of experimental characterizations. Abstract: Graphdiyne (GDY) is a novel two-dimensional carbon isomeric material with a high π⁃conjugation and good electrical conductivity, a tunable natural band gap. Here, the promotion of GDY on the photocatalytic system is investigated by preparing Co-S-P/CuI double S-scheme heterojunctions based on graphdiyne (Cn H2n-2 ). The Co-S-P rough nanosheet structure provides a large number of aiming points for CuI nanoblocks, which effectively prevents the aggregation of CuI nanoblocks. It not only provides a large number of active sites for the reaction, but also facilitates the visible light injection. When GDY is introduced, the three-dimensional structure of GDY/CuI is tightly attached to the Co-S-P surface. On the one hand, the unique two-dimensional/three-dimensional structure is beneficial to promote the mass transfer properties between Co-S-P, GDY and CuI and improve the absorption of visible light. On the other hand, the unique lamellar structure of GDY is like a "tape" connecting Co-S-P and CuI, which not only makes the bond between Co-S-P and CuI tighter, but also serves as a "fabric" to isolate the oxidation sites on the surface of Co-S-P. As a result, the ternary catalyst exhibits excellent hydrogen precipitation stability and photocorrosion resistance. Under 5 W (λ > 420 nm) LED light, CSPGC-20 (135.49 μmol) exhibited the best hydrogen precipitation activity, which is 26.22, 9.2 and 1.6 times higher than that of GDY/CuI (5.32 μmol), Co-S-P (14.72 μmol) and CSPC-20 (85.08 μmol), respectively. This experiment demonstrates the promising potential of Graphdiyne (GDY) for photocatalytic water splitting.